Agricultural Practices in Pakistan: Sustainability and Food Security in a Post-Pandemic Era - Tagar, Hamzo Khan; Barroso, Josué Gutiérrez (Archives of Business Research, 2022)
The key objectives of the paper are to examine the growth sustainability of Pakistan’s agricultural sector in a historical context and its impact on other associated sectors of the economy, particularly on food security. The study also examines major challenges faced by this sector in its growth process making its performance unstable. A descriptive time series analysis is performed on the data obtained from various sources for the period 1951 to 2020. The study finds that the factors like; low investment in this sector, unequal land distributions and utilization of scarce water resources, inadequate supply of major inputs, insufficient infrastructural facilities and unskillful labour force reduce the opportunities for stable agricultural growth in the Indus valley region. It is also evident that duringthe last 70 years period at least ten years of growth was observed instable with negative trends and this phenomenon jolted overall economic indicators that harmed the economic development process at large and impacted food insecurity in Pakistan.